(3gfOSI GdehGfF hGdefTBJ GdHMQjIs - (3YHjOh, EHQGgje Ydjs (1987)
(3GdXhGgQ GdWHjYjI hGdOQGSGJ GdafjI(B.s
(3aj (B: (3gfOSI GdehGfF hGdefTBJ GdHMQjI(B. -(3HjQhJ (B: (3OGQ GdQGJH GdLGeYjI, (B1987. -(3eL(B. 1.s
Keywords: (3GdehGfFs -- (3JUeje hEfTGAs; (3GdgfOSI GdHMQjIs